Neck flexor endurance, craniovertebral angle and neck motion association with and without neck pain: a cross-sectional analytical study - Qureshi, Sameen; Imran Ahmed, Syed; Aftab Ahmed Mirza Baig (Journal of the Pakistan Medical Association, 2026)
Objective: To compare the deep neck flexor endurance, craniovertebral angle and cervical range of motion in individuals with and without mechanical neck pain. Method: The analytical, cross-sectional study was conducted from September 12, 2022, to February 27, 2023, at the Sindh Institute of Physical Medicine and Rehabilitation, Karachi, and comprised adults of either gender aged 18-35 years. Those having nonspecific neck pain were in group A, while group B included healthy individuals without neck pain. The groups were compared in terms of deep neck flexor endurance, craniovertebral angle and cervical range of motion. Data was analysed using SPSS 21. Results: Of the 100 participants, 50(50%) were group A; 25(50%) males and 25(50%) females with mean age 23.643.99 years and mean body mass index 21.433.16kg/m2. The remaining 50(50%) subjects were in group B; 25(50%) males and 25(50%) females with mean age 23.523.97 years and mean body mass index 21.93 4.43kg/m2. Group A showed a significant difference in all range of motion values except rotation. The association of craniovertebral angle and deep neck flexor endurance with neck pain was not significant (p>0.05). Conclusion: Neck pain was not found to be associated with craniovertebral angle, neck rotation and deep neck flexor endurance. However, cervical flexion, extension, left flexion and right flexion were found associated with neck pain. The association of neck pain with age and body mass index was not significant. Key Words: Neck ache, Posture, Movement, Endurance.